Microsoft Office 2000 introductory course - Pasewark, William R.; Patterson, Maurice (Cincinnati, OH : South-Western Educational, 2000)
This book contains: Introduction to Microsoft Word; Microsoft Excel; Microsoft PowerPoint; Microsoft Outlook; Microsoft Publisher & Microsoft Frontpage.
Keywords: Microsoft Office; Computer programs; Microsoft Office; Business -- Computer programs